Matching concepts with measurement - Thurlow, James; Resnick, Danielle; Ubogu, Dumebi (Wiley, 2015)
This paper advocates for a conceptualization of the African middle class that would be universally valid: security from economic vulnerability and prospects for social mobility. We suggest three minimum criteria that are jointly necessary and sufficient to reflect this conceptualization: secondary schooling completion, decent housing amenities and skilled employment. Using household surveys for nine African countries, we then demonstrate how measures of the middle class based on expenditure thresholds refer to households with vastly different abilities to meet these three criteria. This cautions against overreliance on expenditure‐based definitions, which may obscure qualitative differences among the middle class across African countries.